PSYCHOLOGICAL AND METHODS OF DIAGNOSIS PSYCHOPHYSIOLOGICAL EMOTIONAL STATE AND THEIR APPLICATION IN THE PRACTICE OF EDUCATIONAL ORGANIZATIONS - Galina Efremova; Maria Kovaleva; Galina Timoshenko; Elena Leonenko; Irina Bochkovskaya (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the use ofmodern methods ofdiagnostics of emotional states in pedagogical science. The authors examine the current methods such diagnostics, three main groups: using diagnostics instruments; speech analysis means; registration means psychophysiological characteristics. The article also analyzes the various software programs and hardware devices (including medical equipment), which today can be used for the diagnosis of emotions. The possibility of using these methods in pedagogy, assesses their validity and reliability.